Malaysian Islamic Humanitarian Actor: A Case of Global Peace Mission Malaysia (GPM) - Mohd Faridh Hafez Mhd Omar; Sharifah Hayaati Syed Ismail (Universiti Malaya (UM), 2024)
Online Journal of Research in Islamic Studies Vol. 7 No. 2 (2020): 23-36